Effect of Computer-Based Software Package on Students’ Achievement in Graphical Concepts in Mathematics - Etukudo, Udobia Elijah (International Journal on Emerging Mathematics Education, 2018)
This study determined the effects of the Computer Based Software Program Package (CBSPP) for Regular Users of Computer (RUC) and Irregular Users of Computer (IUC) on students’ achievement in graphical concepts in mathematics. It also examined the moderating effects of computer self-efficacy and gender. Skinner’s behaviorist theory provided the framework, while the pretest-posttest control group quasi-experimental design with  factorial matrix was adopted. Two hundred and ninety-six senior secondary II (SS II) students were purposively selected from six schools in Ogba (3), Egbema (2) and Ndoni (1) Local Government Area of Rivers State, Nigeria based on the availability of the computer. Two whole classes each of SS II totaling 97students were randomly assigned to the RUC and given laptop computers to use for the period of the experiment, IUC (99 students) and control group (100 students). Instruments used were: achievement test on the graphical concept () and computer self-efficacy () scales. Instructional guides were also used. Data were analyzed using analysis of covariance and Scheffe post-hoc test at = 0.05. There were significant main effects of treatment on achievement. There were significant main effects of computer self-efficacy on students’ achievement and gender on achievement. There were significant two-way interaction effects of treatment and computer self-efficacy, treatment and gender, computer self-efficacy and gender on students’ achievement. There were significant three-way interaction effects of treatment, gender and computer self-efficacy on students’ achievement in favor of the RUC.